Експериментальне визначення жорсткості багатокоординатного верстата паралельної структури «пентапод» - Шелепко, О. В.; Кириченко, А. М.; Гречка, А. І. (ЦНТУ, 2018)
Роботу присвячено вимірюванню пружних переміщень робочого органа багатокоординатного верстата паралельної структури «пентапод» під навантаженням та експериментальному визначенню матриць просторової жорсткості та податливості. Розроблено схеми вимірювання переміщення робочого органа, який розташований вздовж осі Z при його навантаженні по осям Х, Y та Z. Побудовано залежності похибки переміщення робочого органа від зміни його положення відносно осі Х в діапазоні від -0,075м до 0,075 м, Y = 0, Z = 0 при постійному навантаженні рівному 100 Н вздовж осі Х, Y та Z та визначено матрицю жорсткості на основі результатів отриманих експериментальним шляхом. Работа посвящена измерению упругих перемещений рабочего органа многокоординатного станка параллельной структуры «пентапод» под нагрузкой и экспериментальному определению матриц пространственной жесткости и податливости. Разработаны схемы измерения перемещения рабочего органа, который расположен вдоль оси Z при его нагрузке по осям Х, Y и Z. Построены зависимости погрешности перемещения рабочего органа от изменения его положения относительно оси Х в диапазоне от -0,075м до 0,075 м, Y = 0, Z = 0 при постоянной нагрузке равном 100 Н вдоль оси Х, Y и Z. и определена матрица жесткости на основе результатов полученных экспериментальным путем. The article is devoted to determination of spatial stiffness of the end effector of a pentapod parallel machine tool and its relation to the end effector position into the machine workspace, determination of the compliance and stiffness matrices from experimental measurements data. To study the spatial stiffness of the machine, the method for measuring the displacements of the end effector were developed and a bench for experimental research was produced. On the basis of the results of experimental measurements, the dependence of the end effector displacement upon the change of its position relative to the X axis in the range from -0,075 m to 0,075 m with a constant load equal to 100 N along the X, Y and Z axes. The compliance and stiffness matrices of the machine is calculated on the basis of experimental measurements of the displacements Δx, Δy, Δz of the end effector by computing the nearest symmetric positive definite matrix, which is determined by the Frobenius norm. The experimental stiffness matrix 3x3 is obtained for three positions of the end effector. From the obtained dependences of the displacement of the end effector from its position relative to the X axis under constant load, the maximum displacement along the axes coincides with the direction of the load. Having obtained the compliance and stiffness matrices experimentally for different positions of the end effector, it is shown that the maximum difference in stiffness along the Y axis does not exceed 25%, and along X and Z axes is 14%. The obtained experimental results of the displacement of the end effector in machine workspace under the load force enables further establishment of the areas of the workspace in with the maximum stiffness and helps formulate guidelines to improve the pentapod machine tool spatial stiffness.
Экспериментальное определение жесткости многокоординатного станка параллельной структуры «пентапод»
Еxperimental Determination of Stiffness of Pentapod Parallel Kinematics Machine
Keywords: верстат паралельної структури; робочий орган; пентапод; податливість; жорсткість; податливость; рабочий орган; станок параллельной структуры; пентапод; жесткость; pentapod; end effector; parallel kinematic machine; stiffness; compliance